Eating Problems and Overlap with ADHD and Autism Spectrum Disorders in a Nationwide Twin Study of 9- and 12-Year-Old Children - Maria Råstam; Jakob Täljemark; Armin Tajnia; Sebastian Lundström; Peik Gustafsson; Paul Lichtenstein; Christopher Gillberg; Henrik Anckarsäter; Nóra Kerekes (The Scientific World Journal)
Aim. To establish the prevalence of restrictive eating problems, the overlap and association with attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorders (ASD) and to estimate the heritability of eating problems in a general population sample of twins aged 9 and 12. Methods. Parents of all Swedish 9- and 12-year-old twin pairs born between 1993 and 1998 (n=12,366) were interviewed regarding symptoms of ADHD, ASD, and eating problems (EAT-P). Intraclass correlations and structural equation modelling were used for evaluating the influence of genetic and environmental factors. Cross-twin, cross-trait correlations were used to indicate a possible overlap between conditions. Results. The prevalence of eating problems was 0.6% in the study population and was significantly higher in children with ADHD and/or ASD. Among children with eating problems, 40% were screened positive for ADHD and/or ASD. Social interaction problems were strongly associated with EAT-P in girls, and impulsivity and activity problems with EAT-P in boys. The cross-twin, cross-trait correlations suggested low correlations between EAT-P and ADHD or EAT-P and ASD. Genetic effects accounted for 44% of the variation in liability for eating problems. Conclusions. In the group with eating problems, there was a clear overrepresentation of individuals with ADHD and/or ASD symptoms.